Content analysıs on the graduate theses done about flıpped classroom model ın Turkey - Nayci, Ömer (TURKISH ONLINE JOURNAL OF DISTANCE EDUCATION, 2021)
In this research, it is aimed to examine the graduate theses done about flipped classroom model in Turkey according to some variables. The data of this descriptive study which was conducted by a qualitative research approach was obtained from 105 master’s and doctoral theses accessed from CoHE National Thesis Center database. The data were collected through document analysis and the data were analyzed by content analysis technique. According to the findings, it is determined that the theses were mostly done in 2019, most of the theses were made at Gazi University, the number of master’s theses was more numerous, the studies conducted to examine the effect of flipped classroom model applications on various variables predominate, the model is mostly called as “Flipped classroom model” as in this study and mostly preferred in foreign language education, and in the part where the model is applied at home the most preferred online software is Edmodo. In addition, it was determined that mostly mixed methods were preferred as the research method, university students as sample group, interview form/questions as data collection tool, and “t test” in data analysis. At the end of the research, suggestions were made for researchers and for practitioners.
Keywords: Flipped classroom model; Graduate thesis; Content analysis